Upaya yang Dapat Dilakukan PT. Bintang Distribusi Logistindo untuk Menekan Biaya Klaim dalam Rangka Efisiensi Biaya Usaha - Santoso Sri Handoyo; Mamik Andriani (Universitas Negeri Jakarta, 2008)
The purpose of this research is to know and to understand how the axpedient to must do it PT. Bintang Distribusi Logistindo in to decrease claim cost so that attempt cost to spended to be efficient. Bintang Distribusi Logistindo is the company to move in sector arrangement transportation. In every business attempt always want to find maximal advantage, the method is to efficient cost to spended, with efficient cost the company can give offer low cost and efficient cost so the company can to find maximal advantage. Efficient cost can existance if the company to know source cost superfluous in business activity. The besides, the company too must can do it to press toward cost to spended, in cluded in to efficient cost not to spended. From Results discussion and analysis to mention, that apparently there cost can to press is claim cost especially claim not false freight forwarder, claim cost is claim to deliverer cargo, because there lost and damaged cargo is happened cause there various kinds risk in transport cargo. For to press claim cost there various the expedient to must do it among other things to minimal happened damaged cargo because the part large cause damaged cargo, to examination cargo and document with accurate, to monitor cargo when cargo in handle and the insurance cargo.]